Anti-Fuzzy AB-Ideals - Sassanapitax , Lee; Sriponpaew, Boonyong (Burapha Science Journal, 2026)
In this paper, the concepts of anti-fuzzy AB-ideals of AB-algebras are introduced and some related results are proved. We also study their characterizations by using the concept of lower level subset. Furthermore, we provide the properties of the Cartesian product of anti-fuzzy AB-ideals.